2018
DOI: 10.1123/ijatt.2016-0110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Athletic Trainer Stress and Job Satisfaction with Different Models of Care Delivery

Abstract: Athletic training services are typically delivered by personnel administratively assigned to an athletic department 1 -Role of the team physician and/or athletic trainer (AT) may be influenced by athletic program priorities 2 -Job satisfaction, work-family conflict, job burnout, and intent to leave an organization are interrelated 3 -68% of ATs consider leaving profession due to poor salary, heavy workload, and lack of time for family 1 • Some institutions have replaced the "traditional" athletic program model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Athletic trainers who reported to athletic directors described a lower quality of life due to pressure to make decisions in the interest of coaches and not necessarily the student-athletes. 2 However, many health care providers report to team officials, especially at the highest level of National Collegiate Athletic Association participation. 2 Indeed, health care providers lacked the autonomy to make decisions that were truly in the best interest of their student-athletes, especially when dealing with concussion diagnoses.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Athletic trainers who reported to athletic directors described a lower quality of life due to pressure to make decisions in the interest of coaches and not necessarily the student-athletes. 2 However, many health care providers report to team officials, especially at the highest level of National Collegiate Athletic Association participation. 2 Indeed, health care providers lacked the autonomy to make decisions that were truly in the best interest of their student-athletes, especially when dealing with concussion diagnoses.…”
mentioning
confidence: 99%
“…2 However, many health care providers report to team officials, especially at the highest level of National Collegiate Athletic Association participation. 2 Indeed, health care providers lacked the autonomy to make decisions that were truly in the best interest of their student-athletes, especially when dealing with concussion diagnoses. 3 Further complicating concussion care, many such injuries go unreported by student-athletes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Athletic trainers who report directly to athletic directors and subsequently to coaches have experienced pressure to make timely decisions that affected not only their job status but also their quality of life. 6 Despite the advice of the NATA on the appropriate supervisory structure, ATs and team physicians are still reporting to athletic administration, particularly at the more competitive intercollegiate athletics levels. 6 Previous au-thors [6][7][8][9] have shown that the role of the supervisory structure in interpersonal conflict remains problematic.…”
mentioning
confidence: 99%
“…6 Despite the advice of the NATA on the appropriate supervisory structure, ATs and team physicians are still reporting to athletic administration, particularly at the more competitive intercollegiate athletics levels. 6 Previous au-thors [6][7][8][9] have shown that the role of the supervisory structure in interpersonal conflict remains problematic. An article in the Chronicle of Higher Education 7 highlighted the pressures ATs face regarding return-to-play decisions: more than half of responding collegiate football ATs reported feeling pressure from their football coaches to return concussed players to action before the players were medically ready.…”
mentioning
confidence: 99%